Pengaruh Mucoadhesive Plester Ekstrak Daun Ciplukan (Physalis angulata L.) terhadap Jumlah Limfosit dalam Penyembuhan Ulkus Traumatikus Tikus Putih (Rattus norvegicus) - Astika Swastirani; Cherina Chyntia Ananta S Kembaren (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Traumatic ulcer is an open wound in the oral cavity caused by trauma. Flavonoids in ciplukan leaf have an antiinflammatory effect. Drug delivery using mucoadhesive plasters can increase the effectiveness, absorption, and bioavailability of drugs because directly attached to the wound. Lymphocytes can increase macrophage activation that can accelerate wound healing. The purpose of this research is to determine the effect of mucoadhesive plaster of ciplukan leaf extract (Physalis angulata L.) on the number of lymphocytes in healing traumatic ulcers of white rats (Rattus norvegicus). 30 rats were divided into 5 groups; the negative control group, the positive control group and the treatment group with mucoadhesive plaster ciplukan leaf extract doses of 100, 200, 400 mg/kg BW. Conducting heat induction on the labial mucosa of white rats using an amalgam stopper and then given treatment according to groups. The rats were dissected on day 5. The number of lymphocytes was counted on the preparate with Hematoxylin Eosin staining using an Olympus digital microscope with 400x magnification. The treatment group with mucoadhesive plaster of ciplukan leaf extract dose 100 mg/kg BB had the highest number of lymphocytes, while the positive control group had the lowest number of lymphocytes. The conclusion of this research is mucoadhesive plaster of ciplukan leaf extract (Physalis angulata L.) affects the number of lymphocytes in healing traumatic ulcer of white rats (Rattus norvegicus).